1994
DOI: 10.1088/0954-3899/20/3/005
|View full text |Cite
|
Sign up to set email alerts
|

High-spin states in99Rh

Abstract: High-spin states in 99Rh are populated through a fusion evaporation reaction 16O+89Y. A comprehensive level scheme with four bands is made on the basis of coincidence studies and DCO ratios. Placements of several transitions are revised and, together with five new transitions detected in the experiment, two new bands are proposed. Two other bands populated in the previous work are confirmed. The configurations of the three quasiparticle band-head states of the new bands are suggested as ( pi (g92/)3) and ( pi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
2
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
5
2
1
Order By: Relevance
“…The previously observed positive-parity band B1 based on the 64 keV isomeric state has been extended up to π I = (45/2 + ). The earlier reported part of band B1 [26,27,36] up to 37/2 + state is confirmed in the present work and new ΔI = 1 dipole (M1) transitions have been observed parallel to the earlier reported ΔI = 2 quadrupole (E2) transitions. The 1052-1206-1073-1128−1198 keV E2 transition sequence reported earlier [27] in the high spin part of band B1 is modified in the present level scheme.…”
Section: Positive-parity Bands B1-b3supporting
confidence: 91%
See 4 more Smart Citations
“…The previously observed positive-parity band B1 based on the 64 keV isomeric state has been extended up to π I = (45/2 + ). The earlier reported part of band B1 [26,27,36] up to 37/2 + state is confirmed in the present work and new ΔI = 1 dipole (M1) transitions have been observed parallel to the earlier reported ΔI = 2 quadrupole (E2) transitions. The 1052-1206-1073-1128−1198 keV E2 transition sequence reported earlier [27] in the high spin part of band B1 is modified in the present level scheme.…”
Section: Positive-parity Bands B1-b3supporting
confidence: 91%
“…[301]1 2 orbital. The earlier reported cascade of the 427-552-681-641-813 keV E2 transitions [26,27] and its recent extension by the 985 and 1048 keV transitions by Sugawara et al [36] is confirmed in the present work. The new 1154 and 1376 keV E2 transitions (figure 3(b)) are added to extend band B4 up to ∼8 MeV excitation energy and 37/2 ℏ spin.…”
supporting
confidence: 88%
See 3 more Smart Citations